TINJAUAN YURIDIS TERHADAP KONSUMEN YANG DIRUGIKAN OLEH PELAKU PRAKTIK MONOPOLI (STUDI KASUS TENTANG KARTEL YANG DILAKUKAN OLEH PT YAMAHA DAN PT ASTRA HONDA) - Alparon Azwari; Hayatul Ismi; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Business competition is competition between competition in carrying out production and marketing activities of goods and services. Competition is a strategy to advance the company by producing good quality products through new discoveries and ways to run a better company. This kind of competition is fair competition, where competition is justified by law and brings profits without harming competition. In addition to fair business competition there is unfair business competition, which is business competition that is carried out not in competition, against the law, and against competition.This research is a normative juridical research that conceptualizes law as a norm including values, positive law and court decisions. Legal materials are collected by means of document studies and library research, namely by combining primary, secondary and tertiary legal materials related to unfair business competition law. The analysis of legal materials is carried out by descriptive analysis, namely describing or explaining what it is about a legal event or legal condition based on primary legal norms.The conclusions that can be obtained from the results of the study are First, the Cartel Practices Conducted by PT. Yamaha and PT. Astra That Causes Loss to Consumers Based on Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, namely Article 5 paragraph 1 and Article 47 Paragraph 2 letter f of Law No. 5 of 1999. Second, the legal consequences arising from cartel practices in the price fixing agreement between PT. Yamaha Indonesia Motor Manufacturing and PT. Astra Honda Motor Which Was Decided To Violate Law Number 5 of 1999 In Supreme Court Decision Number: 217 k/pdt.suskppu/2019, namely a fine of Rp. 25 billion and a maximum fine as regulated in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practice and Unfair Business Competition. Keywords: Business Competition, Prohibited Agreements, Cartels, Pricing.